Enhancing Insert Lifetime in Side Cutting of Special Nut Products Using The QCC Method to Reduce Cost Per Piece - Henri Ponda; Suyanto Suyanto (Heuristic, 2025)
This study aims to increase the life time insert SNGX12003-ME used in the side cutting process of special nut products D.8 x 21.5 mm at PT. GM. The main problem identified is the high value of Cost Per Piece (CPP) due to the waste of cutting tools and the lack of classification of insert usage based on material differences, namely K-40 and K-25. To overcome these problems, the Quality Control Circle (QCC) method is used with the PDCA (Plan, Do, Check, Action) cycle approach and the help of the Seven Tools analysis tool. This study uses primary data through observation and interviews, as well as secondary data in the form of insert usage history during January-December 2024. The results showed that the application of additional treatment coating to the insert can significantly increase the life time, which has a direct impact on reducing CPP by up to ±50%. In addition, the classification of insert usage based on material also results in efficiency in stock control and decision-making. These findings prove that the QCC method is effective as a continuous improvement strategy in the manufacturing industry, particularly to lower costs without sacrificing product quality.